2006
DOI: 10.1113/expphysiol.2006.034405
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 release in gastric antral mucosa of guinea‐pigs: basal PGE2 release by cyclo‐oxygenase 2 and ACh‐stimulated PGE2 release by cyclo‐oxygenase 1

Abstract: Prostaglandin E 2 (PGE 2 ), which is generated by two isoforms of cyclo-oxygenase (COX 1 and COX 2 ), is a key mediator in gastric mucosal defense. In the present study, antral mucosa of guineapigs was incubated with various agonists or antagonists in a medium, the PGE 2 concentration of which was measured using a PGE 2 EIA kit. Prostaglandin E 2 was released from the antral mucosa spontaneously (basal PGE 2 release) and acetylcholine (ACh, 10 μM) enhanced the PGE 2 release (ACh-stimulated PGE 2 release) was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Thus, 1 M ACh stimulation induced no increase in the amount of PGE 2 released from the antral mucosae, whereas 10 M ACh stimulation induced a significant increase in it. Similar results have already been reported in the previous report (17).…”
Section: Effects Of Bay-60-7550 (A Pde2 Inhibitor) On Ca 2ϩ -Regulatesupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, 1 M ACh stimulation induced no increase in the amount of PGE 2 released from the antral mucosae, whereas 10 M ACh stimulation induced a significant increase in it. Similar results have already been reported in the previous report (17).…”
Section: Effects Of Bay-60-7550 (A Pde2 Inhibitor) On Ca 2ϩ -Regulatesupporting
confidence: 82%
“…PGE 2 released under the basal condition may activate the PGE 2 autocrine mechanism. Our previous study demonstrated that, in antral mucosae, PGE 2 released under the basal condition are from nonepithelial cells via COX2, those during ACh stimulation are from epithelial cells via COX1, and that, in isolated epithelial cells, the amount of PGE 2 released under the basal condition is negligibly small (17). Because we used isolated antral mucous cells for observing exocytosis, the amount of PGE 2 released under the basal condition is negligibly small.…”
Section: Effects Of Bay-60-7550 (A Pde2 Inhibitor) On Ca 2ϩ -Regulatementioning
confidence: 99%
See 1 more Smart Citation
“…In antral mucous cells, the Ca 2+ -regulated exocytosis which is activated by ACh (acetylcholine) is the main mechanism for mucin release (8,14,15,19) and is modulated by many substances, such as cAMP, NO, cGMP, intracellular Cl − , and arachidonic acid (AA) (8,14,19,(21)(22)(23)(24). NO is synthesized by nitric oxide synthase 1 (NOS1) and enhances the Ca 2+ -regulated exocytosis mediated via cGMP accumulation in antral mucous cells (28).…”
mentioning
confidence: 99%
“…Guinea pigs were sacrificed by intraperitoneal injection of pentobarbital sodium (100 mg/kg), and then, the stomach was removed from the animal. The procedures for the cell preparation have been previously described (8,9,14,15,19,(22)(23)(24). Briefly, the gastric antrum was excised from the stomach, and the mucosal layer was stripped from the muscle layer in cold phosphate buffered saline (4°C) using glass slides.…”
mentioning
confidence: 99%